Pop Up Book Media Intervention Can Improve The Knowledge Of The Dangers Of Smoking Of Elementary School Students In Jambi City - Nurfadillah Wahid; M. Ridwan; Vinna Rahayu Ningsih (International Journal of Health Engineering and Technology, 2023)
Prevention of smoking behavior must be done early, especially in children, one of which provides knowledge about the dangers of smoking in order to avoid smoking behavior. The purpose of this study was to determine the effect of using Pop Up Book media on students' knowledge about the dangers of smoking at State Elementary School 66 / IV Jambi City. This type of research is a quasi-experiment with the planning used, namely One Group, Pre-test and Post-test design. The population of this study amounted to 590 students with a research sample of 34 students. Using the Shapiro Wilk test, the data showed that of the 34 students who only had good knowledge before the intervention, 23 (69.7%) respondents. The results after the intervention, respondents with good knowledge were 28 (84.8%) respondents. This means that knowledge about the dangers of smoking increased in elementary school student respondents. Data tested with the Wilcoxon test can be seen that health education using Pop Up book media about the dangers of smoking is considered very effective with a P Value of 0.000 <0.05, which means statistically there is a difference in increasing knowledge by using Pop Up Book media about the dangers of smoking in elementary school students. The conclusion of this study is that there is an increase in knowledge after intervention using Pop Up Book.